MONITORING OF TECHNICAL STATE OF TECHNOGENIC UNSAFE PIPELINES - Fomichov, S.; Minakov, S.; Minakov, A.; Pirumov, A.; Shevchenko, M.; Chvertko, Ie.; Vovk, O. (Science-based technologies, 2017)
Ukraine has a wide network of main pipelines on its territory. For most of them pre-set operation time has already run out or is close to finishing. This fact together with a potential hazard of technogenic pollution of territory around the pipeline in case of accident rises a problem of monitoring of technical state of pipelines and, as one of possible outcomes, prolongation of operation life of the structure. Authors propose a system able to perform local measurements of mechanical stresses and deformations in the welded structure. Depending on the aim of measurement – single measurement, monitoring of an area, monitoring of the whole pipeline – system has a possibility to change its measuring and data processing sub-systems up to the case when its fully autonomous operation is needed.